Observation of structural color in random Au nano-islands fabricated on dielectric nanopillars - Bae, Young-Gyu; Kim, Taehyun; Lee, Jongsu; Yu, Eui-Sang; Ryu, Yong-Sang; Lee, Seung-Yeol (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Industrial promising structural colors based on subwavelength scale structure inevitably entail very high fabrication costs in artificial implementation. To reduce the costs, we fabricated the microstructure that necessary to realize the structural color through Au nano-islands, which can be manufactured by bottom-up chemical process instead of strict top-down process and developed a device that can adjust color quantitatively. Notably, this device has the color tunability through the refractive index of the solution that infiltrates the device and is expected to be used in the field of sensors or anti-counterfeiting devices.